MORAL EDUCATION FROM THE PERSPECTIVE OF BUYA HAMKA AND IBNU MISKAWAIH IN THE MODERN CONTEXT - Ahmad Faidzal; Nurjanah Nurjanah (Raudhah - Proud To Be Professional, 2023)
This research aims to explore understanding of moral education from the perspective of two main figures, namely Buya Hamka and Ibnu Miskawaih. This research uses qualitative methods with the type of research used is library research. Both are considered classical figures who made significant contributions to Islamic thought, especially related to moral education. This research includes an analysis of Buya Hamka's written works, especially those related to moral education, and Ibnu Miskawaih's works such as "Tahzib al-Akhlaq". A qualitative approach was used to explore the views, values ​​and methods proposed by the two figures in moral education. Text analysis was carried out to identify key concepts, values, and practices that they emphasize in the context of moral education. This research produces an understanding of the relevance of moral education concepts from the perspective of Buya Hamka and Ibnu Miskawaih in a modern context with the aim of producing human behavior with good morals so that it can later be useful in wider society. The practical implications of this research can be used as a basis for developing a holistic and integrated approach to moral education in modern educational institutions. In conclusion, this research contributes to Islamic and educational literature in responding to moral and ethical challenges in modern society.